GAMBARAN PENGETAHUAN REMAJA TENTANG KEPUTIHAN PADA SISWI SMA PASUNDAN KECAMATAN MAJALAYA TAHUN 2020 - Dhebi Nur Safebriyani; Susi Kusniasih; Kamsatun Kamsatun; Bani Sakti (Politeknik Kesehatan Kemenkes Bandung, 2020)
This research is motivated by the problem of vaginal discharge in many adolescents found because of ignorance about the handling of vaginal discharge itself. Lack of knowledge due to lack of information they get from health workers and also dirty environment that can cause vaginal discharge becomes an infection. This problem often occurs in one high school in Majalaya sub-district, one of which is Pasundan High School. This study aims to determine the level of knowledge of adolescents about vaginal discharge in high school students Pasundan Majalaya District in 2020. Knowledge is the result of human sensing, or the result of knowing someone about objects through their senses (eyes, nose, ears, etc.) (Notoatmodjo, 2012). The research method used is descriptive method, with validity testing using Person Product Moment using a questionnaire distributed via Google forms and cluster sampling techniques. The results showed that the characteristics of teenagers in Pasundan High School Majalaya District were mostly 15-16 years old (67.3%). Most of the 59 people (55.1%) who have enough knowledge about vaginal discharge. It is recommended for students to be able to add their insights through electronic media, print, or people around them, especially regarding the causes of vaginal discharge, fungi that cause vaginal discharge, vaginal normal pH, and normal causes of vaginal discharge.